Enhancing early grade reading development: A call for education reform and innovation - Reda Darge Negasi (College of education, Bahir Dar University, 2024)
Welcome to the May issue of Bahir Dar Journal of Education. The present issue is a special issue focusing on the theme "Early Grade Reading Development". In this issue, we present five research articles that examine crucial topics in early-grade reading development. Authored by a total of 13 scholars from four universities in Ethiopia and Norway, the articles provide a comprehensive exploration of the complexities surrounding early-grade reading. They also offer valuable insights into the multifaceted nature of this critical issue and shed light on the various factors that influence early-grade reading development in Ethiopia and beyond.